Haemoglobin A1c, blood pressure and ldl-cholesterol goals attainment and its associated factors among adults with early-onset type 2 diabetes in Terengganu, 2023 - Zulrushdi, Mohd Fariz (2024)
Background: The global and local increase in prevalence of diabetes mellitus presents a significant public health challenge. Early-onset type 2 diabetes, diagnosed between ages 18 and 45 years, is increasingly common and associated with a heightened risk of complications. Therefore, achieving the ABC goals (HbA1c <7%, blood pressure <140/90 mmHg, and LDL-C <100 mg/dL) is essential for managing diabetes and reducing the complications. Objective: This study aims to determine the attainment of two or more ABC goals and its associated factors among adults with early-onset type 2 diabetes in Terengganu in 2023. Methodology: A cross-sectional study design was employed, utilizing secondary data of adults with early-onset type 2 diabetes who were audited in the National Diabetes Registry in Terengganu in 2023. A simple random sampling was applied to select the required sample of 675. Data on sociodemographic characteristics, lifestyle factors, and diabetes treatment profiles were extracted and analysed using SPSS version 28. Descriptive statistics and multiple logistic regression were used to summarize the data and identify factors associated with achieving two or more ABC goals. Results: The mean age of the participants was 46.8 years (SD 7.86). The majority of the patients were female (68.3%), of Malay ethnicity (97.9%), and non-smokers (95.4%). The proportion of attainment two or more goals was 36.4%. Women are 38% less likely than men to achieve two or more ABC goals, with a statistically significant odds ratio (OR) of 0.63 (95% CI: 0.44 to 0.88, p=0.007). Regarding treatment types, individuals on oral treatment alone have 2.49 times higher odds of achieving these goals compared to those on a combination of oral treatment and insulin (95% CI: 1.77 to 3.49, p<0.001). Additionally, those not on any treatment have 2.76 times higher odds of reaching the goals compared to those on the combination treatment (95% CI: 1.11 to 6.91, p=0.030). Conclusion: These findings highlight significant challenges in comprehensive diabetes control among adults with early-onset type 2 diabetes in Terengganu, with notable sex-based disparities and treatment profiles in goal attainment. Effective diabetes management requires addressing gender-specific challenges and modality of treatment profiles through public health campaigns, interdisciplinary strategies, and personalized care. Additionally, achieving the recommended ABC goals is more likely in patients who take fewer medications for diabetes.